Real-time adaptive optics for high-power laser beam correction in the strong turbulence - A.L. Rukosuev; A.N. Nikitin; I.V. Galaktionov; Y.V. Sheldakova; A.V. Kudryashov (Компьютерная оптика)
A combined adaptive optical system designed to correct the wavefront of light radiation distorted by the influence of strong atmospheric turbulence is presented. The system consists of a beam position stabilizer and a fast adaptive optical system operating in real time. Stabilization of the beam position is carried out by two electronically controlled tilt mirrors. The control loop includes two quadrant sensors and an FPGA (field-programmable gate array) that closes the feedback loop. Using information received from Shack-Hartmann wavefront sensor, a bimorph-based adaptive mirror, controlled by another FPGA, is able to compensate for wavefront aberrations for up to 23-th Zernike polynomial in real time. The system was tested under the laboratory turbulence conditions created by a fan heater. The bandwidth of the artificial turbulence in the experiments did not exceed 100 Hz, which corresponds to the average statistical state of the real atmosphere. Results of the correction of the wave front distorted by the artificial turbulence are presented. It is shown that when only a bimorph corrector is used, the value of wavefront tilt angles increases. This presents a certain problem, since a significant part of the turbulence energy falls on the wave front tilts. To address this problem, it is proposed additionally using a system for stabilizing the position of the light beam.